Polyester-based pressure-sensitive adhesive composition, polyester-based pressure-sensitive adhesive, and pressure-sensitive adhesive sheet
The use of a petroleum resin-based tackifier with a specific molecular weight in a polyester adhesive composition addresses compatibility and tackability issues, resulting in enhanced adhesive strength and retention for electronic and optical applications.
Patent Information
- Application Number
- JP2021025277
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-27
- Filing Date
- 2021-02-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-02-19
AI Technical Summary
Existing polyester-based adhesive compositions using tackifiers with high softening points, such as rosin ester and terpene resins, face issues like reduced tackability at room temperature, yellowing, and compatibility problems with polyester resins.
A polyester adhesive composition is developed using a petroleum resin-based tackifier with a specific number average molecular weight of 400 to 8,000, blended with a polyester resin containing structural units derived from polyvalent carboxylic acids and polyol, to achieve excellent adhesive strength and retention.
The composition exhibits superior adhesive strength, retention, and tackability, making it particularly suitable for electronic and optical applications.
Smart Images

Figure 0007661718000001 
Figure 0007661718000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester-based pressure-sensitive adhesive composition, a polyester-based pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet, and more specifically to a polyester-based pressure-sensitive adhesive composition, a polyester-based pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet which have excellent adhesive strength to various adherends and further excellent holding power and tackiness. [Background technology]
[0002] It has been known that polyester-based resins, when combined with a polycarboxylic acid component and a polyol component, have excellent chemical resistance, plasticizer resistance, mechanical strength, etc., and this has also been studied in the field of adhesives (pressure-sensitive adhesives).
[0003] Moreover, in recent years, with the miniaturization and thinning of parts and components, adhesives are also required to have high adhesive strength even over a small area. As a method for improving adhesive strength, for example, Patent Document 1 proposes a polyester-based adhesive composition containing a polyester and a tackifier. Furthermore, Patent Document 2 proposes a polyester-based pressure-sensitive adhesive composition containing a polyester, a hydrolysis stabilizer, a tackifier, and a crosslinking agent, the polyester-based pressure-sensitive adhesive composition containing 20 to 100 parts by weight of a tackifier having a specific acid value and a specific softening point per 100 parts by weight of the polyester. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-169419 A [Patent Document 2] JP 2015-134906 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, the techniques disclosed in Patent Documents 1 and 2 incorporate a tackifier with a high softening point, such as a rosin ester or a terpene resin. In general, a tackifier with a high softening point is often incorporated to impart cohesive strength at high temperatures, but such a tackifier has problems such as reduced tack at room temperature and changes in appearance, such as yellowing and cloudiness. Furthermore, the terpene resin-based tackifiers described in Patent Documents 1 and 2 have low polarity, and there are concerns about compatibility with polyester resins.
[0006] Under these circumstances, the present invention aims to provide a polyester-based pressure-sensitive adhesive composition that has excellent adhesion to various adherends and also has excellent holding power and tackiness, and further aims to provide a polyester-based pressure-sensitive adhesive and a pressure-sensitive adhesive sheet. [Means for solving the problem]
[0007] However, in light of these circumstances, the present inventors conducted extensive research and discovered that, in a polyester-based pressure-sensitive adhesive composition containing a polyester resin and a tackifier, by using a petroleum resin-based tackifier having a specific number average molecular weight in a specific content ratio as the tackifier, it is possible to obtain a polyester-based pressure-sensitive adhesive composition that has excellent adhesion to various adherends as well as excellent holding power and tackiness, and thus completed the present invention.
[0008] That is, a first gist of the present invention is a polyester-based pressure-sensitive adhesive composition comprising a polyester-based resin (A) having a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2), and a petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8000, wherein the content of the petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8000 is 0.01 to 50 parts by weight per 100 parts by weight of the polyester resin (A).
[0009] A second gist of the present invention is a polyester-based pressure-sensitive adhesive obtained by crosslinking the polyester-based pressure-sensitive adhesive composition, and a third gist of the present invention is a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing the polyester-based pressure-sensitive adhesive.
[0010] In polyester-based adhesives, generally, a tackifier is blended to improve the adhesive strength to the adherend. In this case, a conventionally known tackifier, such as terpene resin, phenolic resin, rosin resin, aliphatic petroleum resin, aromatic petroleum resin, copolymerized petroleum resin, alicyclic petroleum resin, xylene resin, epoxy resin, polyamide resin, ketone resin, elastomer resin, etc., can be used. Generally, terpene resin and rosin resin are often used from the viewpoint of adhesive strength and tackiness, while there are problems such as poor compatibility with polyester-based resin and hydrolysis proceeding due to high acid value. In addition, petroleum resin is considered not to be practically used because of its low polarity, poor compatibility with highly polar polyester-based resin and low tackiness. However, in the present invention, when a polyester resin is used as the base resin, a petroleum resin tackifier is deliberately blended with the polyester resin. As a result, unexpectedly, the adhesive strength and tackiness are not reduced, and rather, the adhesive strength, holding power and tackiness are excellent, and the object of the present invention can be achieved. Effect of the Invention
[0011] The polyester-based adhesive composition of the present invention contains a polyester-based resin (A) having a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2) and a petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8000, and the content of the petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8000 is 0.01 to 50 parts by weight per 100 parts by weight of the polyester-based resin (A). Therefore, it has excellent adhesion to various adherends, and further has excellent holding power and tackiness, and is particularly useful as an adhesive for electronic components and optical components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The configuration of the present invention will be described in detail below, but these are merely examples of preferred embodiments. In the present invention, the term "carboxylic acids" includes not only carboxylic acids but also carboxylic acid derivatives such as carboxylic acid salts, carboxylic acid anhydrides, carboxylic acid halides, and carboxylic acid esters.
[0013] The polyester-based pressure-sensitive adhesive composition of the present invention contains a polyester-based resin (A) and a petroleum resin-based tackifier (B) having a specific number average molecular weight in a specific content ratio. Each component contained in the polyester-based pressure-sensitive adhesive composition of the present invention will be described below.
[0014] <Polyester resin (A)> The polyester resin (A) has, as its resin composition, structural units derived from a polyvalent carboxylic acid (a1) and structural units derived from a polyol (a2), and is usually obtained by copolymerizing copolymerization components containing the polyvalent carboxylic acid (a1) and the polyol (a2) as constituent raw materials.
[0015] [Polyvalent carboxylic acids (a1)] The polyvalent carboxylic acids (a1) used as the raw material for the polyester resin (A) include, for example, divalent dicarboxylic acids and trivalent or higher polyvalent carboxylic acids, and dicarboxylic acids are preferably used because the polyester resin (A) can be stably obtained. The polyvalent carboxylic acids (a1) can be used alone or in combination of two or more kinds.
[0016] Examples of the dicarboxylic acids include aliphatic dicarboxylic acids such as malonic acids, dimethylmalonic acids, succinic acids, glutaric acids, adipic acids, trimethyladipic acids, pimelic acids, 2,2-dimethylglutaric acids, azelaic acids, sebacic acids, fumaric acids, maleic acids, itaconic acids, thiodipropionic acids, diglycolic acids, and 1,9-nonanedicarboxylic acids; Aromatic dicarboxylic acids (a1-1), such as phthalic acids, terephthalic acids, isophthalic acids, benzylmalonic acids, diphenic acids, 4,4'-oxydibenzoic acids, and further naphthalenedicarboxylic acids such as 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, and 2,7-naphthalenedicarboxylic acids; Alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acids, 1,2-cyclohexanedicarboxylic acids, 1,3-cyclopentanedicarboxylic acids, 1,4-cyclohexanedicarboxylic acids, 2,5-norbornanedicarboxylic acids, and adamantanedicarboxylic acids; Structural units derived from dimer acids (mainly those having 36 to 44 carbon atoms) derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc.; and the like.
[0017] Examples of the trivalent or higher polyvalent carboxylic acids include trimellitic acids, pyromellitic acids, adamantanetricarboxylic acids, and trimesic acids.
[0018] In addition, as the polyvalent carboxylic acid (a1), a compound containing a hydrogenated polybutadiene structure may be used, for example, polybutadiene-based polyvalent carboxylic acids such as 1,2-polybutadiene dicarboxylic acids, 1,4-polybutadiene dicarboxylic acids, 1,4-polyisoprene dicarboxylic acids, etc., or saturated hydrocarbon-based polyvalent carboxylic acids in which the double bonds of these polybutadiene-based polyvalent carboxylic acids are saturated with hydrogen or halogen, etc. can be mentioned. Furthermore, polyvalent carboxylic acids in which olefin compounds such as styrene, ethylene, vinyl acetate, and acrylic acid esters are copolymerized with polybutadiene-based polyvalent carboxylic acids, or hydrogenated polyvalent carboxylic acids thereof can also be used. Among them, hydrocarbon-based polybutadiene polyvalent carboxylic acids with a high degree of saturation are preferred, and those having a number average molecular weight of 300 to 30,000, particularly 500 to 10,000, and further 800 to 5,000 are preferred, and those having an average functionality of 1.5 to 3 of carboxy groups are preferred.
[0019] The hydrogenated polybutadiene structure-containing compound preferably has a higher ratio of 1,2 bond sites among 1,2 bond sites and 1,4 bond sites in the hydrogenated polybutadiene structure in terms of excellent adhesion to polyolefin substrates. The ratio of 1,2 bond sites in the hydrogenated polybutadiene structure is preferably 25 to 100%, more preferably 50 to 100%, and even more preferably 75 to 100%.
[0020] Among the above polyvalent carboxylic acids (a1), the aromatic dicarboxylic acids (a1-1) are preferred because of their excellent adhesive strength and holding power.
[0021] Furthermore, among the above aromatic dicarboxylic acids (a1-1), it is preferable to include asymmetric aromatic dicarboxylic acids (a1-1-1) from the viewpoint of reducing the crystallinity of the polyester resin (A). Examples of the asymmetric aromatic dicarboxylic acids (a1-1-1) include phthalic acids, isophthalic acids, 1,8-naphthalenedicarboxylic acids, 2,3-naphthalenedicarboxylic acids, and 2,7-naphthalenedicarboxylic acids. Among these, isophthalic acids are particularly preferable from the viewpoint of reactivity.
[0022] The content of the asymmetric aromatic dicarboxylic acid (a1-1-1) is preferably 0.1 to 70 mol%, more preferably 0.5 to 60 mol%, further preferably 1 to 50 mol%, particularly preferably 2 to 40 mol%, particularly preferably 3 to 30 mol%, and most preferably 5 to 20 mol% based on the total polyvalent carboxylic acid (a1). If the content is too low, the resin tends to crystallize and sufficient adhesive performance cannot be obtained, while if the content is too high, the initial adhesive strength (tack) tends to decrease.
[0023] In the present invention, from the viewpoint of improving the initial adhesive strength (tack), it is preferable to contain, as the polyvalent carboxylic acids (a1), aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms (including the carbon of the carboxy group), and it is more preferable to contain aliphatic dicarboxylic acids having 6 to 12 carbon atoms (including the carbon of the carboxy group). It is particularly preferable to contain adipic acids, sebacic acids, and azelaic acids, and it is especially preferable to contain sebacic acids from the viewpoint of excellent adhesive strength when a petroleum resin-based tackifier resin (B) described later is used.
[0024] The content of the aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms is preferably 5 to 100 mol%, more preferably 20 to 99 mol%, further preferably 40 to 98 mol%, particularly preferably 60 to 97 mol%, and particularly preferably 80 to 95 mol%, based on the total polyvalent carboxylic acids (a1). If the content is too low, the glass transition temperature of the polyester resin (A) becomes too high, and sufficient adhesive strength tends to be difficult to obtain. If the content is too high, the resin tends to crystallize, and sufficient adhesive performance tends to be difficult to obtain.
[0025] In the present invention, from the viewpoint of adhesive properties, it is also preferable to use asymmetric aromatic dicarboxylic acids (a1-1-1) and aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms in combination as polyvalent carboxylic acids (a1). The content ratio (molar ratio) of the asymmetric aromatic dicarboxylic acids (a1-1-1) and the aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms is preferably (a1-1-1) / (a1-2)=0.1 / 99.9 to 70 / 30, more preferably 0.5 / 99.5 to 60 / 40, even more preferably 1 / 99 to 50 / 50, particularly preferably 2 / 98 to 40 / 60, particularly preferably 3 / 97 to 30 / 70, and most preferably 5 / 95 to 20 / 80.
[0026] For the purpose of increasing the number of branching points in the polyester resin (A), trivalent or higher polyvalent carboxylic acids can also be used. Among these, trimellitic acids are preferably used because they are relatively less likely to cause gelation.
[0027] The content of such trivalent or higher polyvalent carboxylic acids is preferably 10 mol % or less, particularly preferably 0.1 to 5 mol %, based on the total amount of polyvalent carboxylic acids (a1), in order to increase the cohesive strength of the adhesive. If the content is too high, gelation tends to occur easily during the production of the polyester resin (A).
[0028] [Polyol (a2)] Examples of the polyol (a2) used as a constituent raw material of the polyester resin (A) include dihydric diols, trihydric or higher polyols, etc. The polyol (a2) can be used alone or in combination of two or more kinds.
[0029] Examples of the diol include aliphatic diols such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dipropylene glycol, 1,3-propanediol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, and 2,2,4-trimethyl-1,6-hexanediol; Alicyclic diols such as 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, spiroglycol, tricyclodecane dimethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol; Examples of the aromatic diols include 4,4'-thiodiphenol, 4,4'-methylenediphenol, bisphenol, bisphenolfluorene, 4,4'-dihydroxybiphenyl, o-, m- and p-dihydroxybenzene, 2,5-naphthalenediol, and p-xylenediol; and ethylene oxide and propylene oxide adducts thereof. Further examples include fatty acid esters derived from castor oil, dimer diols derived from oleic acid, erucic acid, and the like, and glycerol monostearate.
[0030] Examples of the trihydric or higher polyol include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.
[0031] As the polyol (a2), a hydrogenated polybutadiene polyol (a2-1) can be used. Examples of the hydrogenated polybutadiene polyol (a2-1) include polybutadiene polyols such as 1,2-polybutadiene polyol, 1,4-polybutadiene polyol, and 1,4-polyisoprene polyol, and saturated hydrocarbon polyols in which the double bonds of these polybutadiene polyols are saturated with hydrogen or halogen. Furthermore, polyols in which olefin compounds such as styrene, ethylene, vinyl acetate, and acrylic acid esters are copolymerized with polybutadiene polyols, and hydrogenated polyols thereof can also be used. Among these, hydrocarbon polybutadiene polyols with a high degree of saturation are preferred, and those having a number average molecular weight of 300 to 30,000, more preferably 500 to 10,000, and even more preferably 800 to 5,000, and an average functionality of hydroxyl groups of 1.5 to 3 are preferred.
[0032] The hydrogenated polybutadiene polyol (a2-1) preferably has a higher ratio of 1,2 bond sites among 1,2 bond sites and 1,4 bond sites in the hydrogenated polybutadiene structure in terms of excellent adhesion to polyolefin substrates. The ratio of 1,2 bond sites in the hydrogenated polybutadiene structure is preferably 25 to 100%, more preferably 50 to 100%, and even more preferably 75 to 100%.
[0033] Among the above polyols (a2), it is preferable to use the hydrogenated polybutadiene polyol (a2-1) because of its excellent adhesion to polyolefin substrates.
[0034] The content of the hydrogenated polybutadiene polyol (a2-1) is preferably 0.001 to 15 mol%, more preferably 0.005 to 10 mol%, further preferably 0.01 to 5 mol%, particularly preferably 0.05 to 2 mol%, and particularly preferably 0.1 to 1 mol% relative to the polyol (a2). If the content is too low, the adhesion to the polyolefin substrate tends to decrease, and if the content is too high, the compatibility tends to decrease.
[0035] In addition, it is preferable that the polyol (a2) contains a branched structure-containing polyol (a2-2) in order to increase the branching points and break the crystallinity. Examples of the branched structure-containing polyol (a2-2) include neopentyl glycol, 2-methyl-1,3-propanediol, 2-methyl-2-ethyl-1,3-propanediol, 2,2-diethyl-1,3-propanediol, 2-methyl-2-propyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,3,5-trimethyl-1,3-pentanediol, 2-methyl-1,6-hexanediol, and dimer diol. Among them, neopentyl glycol is particularly preferable. The branched structure-containing polyol (a2-2) is one other than the above-mentioned hydrogenated polybutadiene polyol (a2-1).
[0036] The content of the branched structure-containing polyol (a2-2) is preferably 5 to 100 mol % based on the total polyol (a2), more preferably 10 to 90 mol %, further preferably 20 to 80 mol %, particularly preferably 30 to 70 mol %, and particularly preferably 40 to 60 mol %. If the content is too low, the resin tends to crystallize and it is difficult to obtain sufficient adhesive performance. If the content is too high, the reaction time tends to be long in the production of the polyester resin (A).
[0037] On the other hand, it is preferable that the polyol (a2) contains a linear polyol (a2-3) from the viewpoint of reactivity, and more preferably, a linear polyol having 2 to 40 carbon atoms. Examples of such linear polyol (a2-3) include aliphatic glycols such as ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, 1,9-nonanediol, 1,10-decanediol, and 1,12-dodecanediol. Among them, ethylene glycol, 1,4-butanediol, and 1,6-hexanediol are particularly preferable.
[0038] The content of the linear polyol (a2-3) is preferably 5 to 100 mol %, more preferably 10 to 90 mol %, further preferably 20 to 80 mol %, and particularly preferably 30 to 60 mol %, based on the total polyol (a2). If the content is too low, it tends to be difficult to obtain a stable resin formation.
[0039] It is also preferable to use a trivalent or higher polyol for the purpose of increasing the branching points in the polyester resin (A). Examples of trivalent or higher polyols include pentaerythritol, dipentaerythritol, tripentaerythritol, glycerin, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantanetriol.
[0040] The content of the trihydric or higher polyol is preferably 20 mol % or less, more preferably 0.1 to 10 mol %, and particularly preferably 0.5 to 5 mol %, based on the total content of the polyol (a2). If the content is too high, the production of the polyester resin (A) tends to become difficult.
[0041] The polyester resin (A) used in the present invention is produced by arbitrarily selecting the above polyvalent carboxylic acids (a1) and polyol (a2) and subjecting them to a polycondensation reaction in the presence of a catalyst by a known method.
[0042] The mixing ratio of the polyvalent carboxylic acid (a1) and the polyol (a2) is preferably 1 to 3 equivalents of the polyol (a2) per equivalent of the polyvalent carboxylic acid (a1), and particularly preferably 1.1 to 2 equivalents. If the mixing ratio of the polyol (a2) is too low, the acid value tends to be high, making it difficult to increase the molecular weight, and if it is too high, the yield tends to decrease.
[0043] In the above polycondensation reaction, an esterification reaction is carried out first, and then the polycondensation reaction is carried out. In such an esterification reaction, a catalyst is used, and specific examples thereof include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, and catalysts such as zinc acetate, manganese acetate, and dibutyltin oxide, and one or more of these are used. Among these, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred from the perspective of the balance between high catalytic activity and hue.
[0044] The amount of the catalyst is preferably 1 to 10,000 ppm, particularly preferably 10 to 5,000 ppm, and further preferably 20 to 3,000 ppm, based on the total copolymerization components. If the amount is too small, the polymerization reaction tends not to proceed sufficiently, whereas if the amount is too large, there is no advantage such as shortening the reaction time, and side reactions tend to occur easily.
[0045] The reaction temperature during the esterification reaction is preferably 200 to 300° C., particularly preferably 210 to 280° C., and further preferably 220 to 260° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if the reaction temperature is too high, side reactions such as decomposition tend to occur easily. The pressure during the reaction is usually normal pressure.
[0046] After the esterification reaction, a polycondensation reaction is carried out. As reaction conditions for the polycondensation reaction, it is preferable to further compound the same amount of the catalyst as that used in the above esterification reaction, set the reaction temperature at preferably 220 to 280° C., particularly preferably 230 to 270° C., and gradually reduce the pressure of the reaction system to finally carry out the reaction at 5 hPa or less. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, and if it is too high, side reactions such as decomposition tend to occur easily.
[0047] Thus, the polyester resin (A) used in the present invention is obtained.
[0048] The polyester resin (A) generally has structural units derived from polycarboxylic acids (a1) and structural units derived from polyols (a2). When the structural units derived from asymmetric aromatic dicarboxylic acids (a1-1-1) are contained as structural units derived from polycarboxylic acids (a1), the structural units derived from asymmetric aromatic dicarboxylic acids (a1-1-1) are preferably contained in an amount of 0.1 to 70 mol %, more preferably 0.5 to 60 mol %, even more preferably 1 to 50 mol %, particularly preferably 2 to 40 mol %, especially preferably 3 to 30 mol %, and most preferably 5 to 20 mol % in the structural units derived from polycarboxylic acids (a1).
[0049] In addition, when structural units derived from aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms are contained as structural units derived from polycarboxylic acids (a1), the structural units derived from aliphatic dicarboxylic acids (a1-2) having 4 or more carbon atoms are contained in the structural units derived from polycarboxylic acids (a1) in an amount of preferably 5 to 100 mol %, more preferably 20 to 99 mol %, even more preferably 40 to 98 mol %, particularly preferably 60 to 97 mol %, and especially preferably 80 to 95 mol %.
[0050] In addition, when the polyester resin (A) contains a structural unit derived from a compound having a hydrogenated polybutadiene structure, the content of the structural unit derived from the compound having a hydrogenated polybutadiene structure in the polyester resin (A) is preferably 0.01 to 50% by weight, more preferably 0.1 to 30% by weight, even more preferably 0.2 to 20% by weight, particularly preferably 0.3 to 10% by weight, especially preferably 0.4 to 5% by weight, and most preferably 0.5 to 2% by weight.
[0051] In terms of adhesion to polyolefin substrates, the structural unit derived from the hydrogenated polybutadiene structure-containing compound in the polyester resin (A) is preferably contained as at least one of a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2), and more preferably contained as a structural unit derived from a polyol (a2).
[0052] Furthermore, when the structural units derived from the hydrogenated polybutadiene polyol (a2-1) are contained as structural units derived from the polyol (a2), from the viewpoint of compatibility, the structural units derived from the hydrogenated polybutadiene polyol (a2-1) are contained in an amount of preferably 0.001 to 15 mol %, more preferably 0.005 to 10 mol %, further preferably 0.01 to 5 mol %, particularly preferably 0.05 to 2 mol %, and particularly preferably 0.1 to 1 mol % in the structural units derived from the polyol (a2).
[0053] On the other hand, when the structural units derived from the branched structure-containing polyol (a2-2) are contained as structural units derived from the polyol (a2), in terms of disrupting the crystallinity of the polyester resin (A), the structural units derived from the branched structure-containing polyol (a2-2) are preferably contained in an amount of 5 to 100 mol %, more preferably 10 to 90 mol %, even more preferably 20 to 80 mol %, particularly preferably 30 to 70 mol %, and especially preferably 40 to 60 mol % in the structural units derived from the polyol (a2).
[0054] When the structural units derived from the linear polyol (a2-3) are contained as structural units derived from the polyol (a2), from the viewpoint of stable resin formation, the structural units derived from the linear polyol (a2-3) are contained in an amount of preferably 5 to 100 mol %, more preferably 10 to 90 mol %, further preferably 20 to 80 mol %, and particularly preferably 30 to 60 mol % in the structural units derived from the polyol (a2).
[0055] Here, the proportion of structural units (compositional proportion) derived from each component of the polyester resin (A) can be determined, for example, by NMR.
[0056] The glass transition temperature of the polyester resin (A) is preferably −80 to 20° C. from the viewpoint of adhesive properties, particularly preferably −75 to 10° C., further preferably −70 to −20° C., more preferably −65 to −30° C., particularly preferably −60 to −35° C., and most preferably −55 to −40° C. If the glass transition temperature is too high, flexibility is lost, initial adhesiveness decreases, adhesive strength is difficult to exert with pressure of the order of finger pressure, and workability tends to decrease, whereas if the glass transition temperature is too low, cohesive strength decreases, the adhesive sheet becomes susceptible to deformation, and the appearance tends to be impaired.
[0057] Here, the glass transition temperature (Tg) of the polyester resin (A) is a value measured using a differential scanning calorimeter DSC Q20 manufactured by TA Instruments. The measurement temperature range is −90 to 100° C., and the temperature rise rate is 10° C. / min.
[0058] The ester bond concentration of the polyester resin (A) is preferably 3 to 9 mmol / g, more preferably 4 to 9 mmol / g, further preferably 4.5 to 8.5 mmol / g, and particularly preferably 5 to 8 mmol / g. If the ester bond concentration is too low, the polyester resin (A) tends to become soft and the adhesive properties tend to decrease. If the ester bond concentration is too high, the polyester resin (A) tends to become hard and the adhesive properties tend to decrease.
[0059] The ester bond concentration (mmol / g) refers to the number of moles of ester bonds in 1 g of polyester resin, and is calculated from the amount of each resin, for example. The calculation method is to divide the number of moles of the polyvalent carboxylic acid (a1) or the polyol (a2), whichever is charged in smaller amount, by the total weight, and an example of the calculation formula is shown below. When the polyvalent carboxylic acids (a1) and the polyol (a2) are charged in equal molar amounts, either of the following calculation formulas may be used. Furthermore, when a monomer having both a carboxyl group and a hydroxyl group is used, or when polyester is produced from caprolactone or the like, the calculation method will be changed appropriately.
[0060] <When the amount of polyvalent carboxylic acid (a1) is less than the amount of polyol (a2)> Ester bond concentration (mmol / g) = [(A1 / a1 × m1 + A2 / a2 × m2 + A3 / a3 × m3 ) / Z] × 1000 A1, A2, A3: Amount of polyvalent carboxylic acid (a1) (g) a1, a2, a3...: molecular weight of polyvalent carboxylic acid (a1) m1, m2, m3: number of carboxy groups per molecule of polyvalent carboxylic acid (a1) Z: Finished weight (g) <When the amount of polyol (a2) is less than the amount of carboxylic acid (a1)> Ester bond concentration (mmol / g) = [(B1 / b1 × n1 + B2 / b2 × n2 + B3 / b3 × n3 ) / Z] × 1000 B1, B2, B3: Amount of polyol (a2) (g) b1, b2, b3: molecular weight of polyol (a2) n1, n2, n3: number of hydroxyl groups per molecule of polyol (a2) Z: Finished weight (g)
[0061] The ester bond concentration can also be measured by a known method such as NMR. For example, the ester group concentration of polyester resin (A) is 1 H-NMR measurement (proton nuclear magnetic resonance spectroscopy), 13 This can be done by C-NMR measurement (carbon-type nuclear magnetic resonance spectroscopy).
[0062] From the viewpoint of storage stability, it is preferable that the polyester resin (A) does not crystallize. Even if it does crystallize, it is preferable that the heat of crystalline fusion of the polyester resin (A) is as low as possible, and is usually 35 J / g or less, preferably 20 J / g or less, particularly preferably 10 J / g or less, especially preferably 5 J / g or less, more preferably 3 J / g or less, and most preferably 1 J / g or less. The heat of crystallization and fusion is the change in energy when a crystallized solid substance changes into a liquid state, and can be measured by a differential scanning calorimeter (DSC).
[0063] The acid value of the polyester resin (A) is preferably 10 mgKOH / g or less, particularly 3 mgKOH / g or less, more preferably 1.5 mgKOH / g or less, and even more preferably 1 mgKOH / g or less. If the acid value is too high, hydrolysis tends to proceed and the cohesive strength tends to decrease.
[0064] The hydroxyl value of the polyester resin (A) is preferably 50 mgKOH / g or less, particularly 30 mgKOH / g or less, further 20 mgKOH / g or less, and more preferably 15 mgKOH / g or less. If the hydroxyl value is too high, the crosslinking efficiency with the crosslinking agent (D) described later tends to decrease.
[0065] The acid value and hydroxyl value of the polyester resin (A) are determined by neutralization titration in accordance with JIS K0070.
[0066] The weight average molecular weight of the polyester resin (A) is preferably 5,000 to 300,000 from the viewpoint of the cohesive strength of the adhesive, particularly preferably 8,000 to 200,000, further preferably 10,000 to 120,000, and especially preferably 30,000 to 100,000. If the weight average molecular weight is too small, the adhesive will not have sufficient cohesive strength and the heat resistance and mechanical strength will tend to be easily reduced, whereas if it is too large, the polyester resin (A) will be easily gelled during production, and the resin will tend to be difficult to obtain.
[0067] The number average molecular weight of the polyester resin (A) is preferably 3000 to 100000, more preferably 4000 to 800000, still more preferably 5000 to 50000, particularly preferably 6000 to 30000, and especially preferably 7000 to 20000. If the number average molecular weight is too small, sufficient cohesive strength as a pressure-sensitive adhesive cannot be obtained, and heat resistance and mechanical strength tend to be easily reduced, whereas if it is too large, adhesion to the substrate tends to be reduced.
[0068] The weight average molecular weight and number average molecular weight in the present invention are based on the molecular weight of standard polystyrene. The high performance liquid chromatograph (HLC-8320GPC, manufactured by Tosoh Corporation) was used with a column: TSKgel SuperMultipore HZ-M (exclusion limit molecular weight: 2×10 6 The measurement is performed using two columns in series (theoretical plate number: 16,000 plates / column, filler material: styrene-divinylbenzene copolymer, filler particle size: 4 μm).
[0069] <Petroleum resin-based tackifier (B)> The polyester-based adhesive composition of the present invention contains the above-mentioned polyester-based resin (A) and a petroleum resin-based tackifier (B) having a specific number-average molecular weight. As described above, petroleum resin-based tackifiers have low polarity and are poorly compatible with polyester-based resins having high polarity, so it is generally difficult to mix and use them. This is even more difficult when trying to improve tackiness. However, the present invention has found that when the polyester-based resin (A) is used as the base resin, a polyester-based adhesive composition excellent in adhesion, retention and tackiness can be obtained by blending the polyester-based resin (A) and a petroleum resin-based tackifier (B) having a specific number-average molecular weight at a specific content ratio.
[0070] The number average molecular weight of the petroleum resin-based tackifier (B) is 400 to 8000. It is preferably 500 to 5000, more preferably 600 to 3000, particularly preferably 700 to 2000, and especially preferably 750 to 1500. When the number average molecular weight of the petroleum resin-based tackifier (B) is within the above range, it is excellent in adhesion, holding power, and tackiness. The number average molecular weight of the petroleum resin-based tackifier (B) can be measured by the same method as that of the polyester resin (A) described above.
[0071] The weight average molecular weight of the petroleum resin tackifier (B) is preferably 400 to 10,000, particularly 600 to 8,000, further 800 to 4,000, and particularly 1,000 to 2,000. When the weight average molecular weight of the petroleum resin tackifier (B) is within the above range, the petroleum resin tackifier has excellent adhesive strength, holding power, and tackiness. The weight average molecular weight of the petroleum resin tackifier (B) can be measured by the same method as that of the polyester resin (A) described above.
[0072] Examples of the petroleum resin-based tackifier (B) include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, hydrogenated petroleum resins obtained by hydrogenating these, alicyclic petroleum resins such as dicyclopentadiene, coumarone-indene resins, etc. These may be used alone or in combination of two or more.
[0073] Among the petroleum resin-based tackifiers (B), those having an aromatic ring structure are preferred from the viewpoint of excellent adhesion, retention and tackiness, and aromatic (C9) petroleum resins and aliphatic / aromatic copolymer (C5 / C9) petroleum resins are more preferred, and aliphatic / aromatic copolymer (C5 / C9) petroleum resins are particularly preferred. Among these, it is preferred that the aromatic ring structure is derived from a styrene resin.
[0074] The styrene resin is preferably a styrene polymer, but may be a mixture of a styrene monomer and a styrene polymer. The styrene polymer may be a homopolymer or copolymer of one or more styrene monomers, or a copolymer of one or more styrene monomers and a monomer other than the styrene monomer.
[0075] Examples of the styrene-based polymer include polystyrene, polyα-methylstyrene, a copolymer of α-methylstyrene and styrene, a copolymer of a styrene-based monomer and an aliphatic monomer, a copolymer of a styrene-based monomer and an aromatic monomer, a copolymer of α-methylstyrene and a styrene-based monomer other than α-methylstyrene, etc. Among these, from the viewpoint of excellent adhesion, retention, and tackiness, a copolymer of a styrene-based monomer and a copolymer of a styrene-based monomer and an aliphatic monomer are preferred.
[0076] Examples of the styrene-based monomer include alkyl-substituted styrenes such as styrene, 2-methylstyrene, 4-methylstyrene, 4-ethylstyrene, 4-t-butylstyrene, and 2,4-dimethylstyrene; α-alkyl-substituted styrenes such as α-methylstyrene and α-methyl-4-methylstyrene; and substituted styrenes such as 2-chlorostyrene, 4-chlorostyrene, hydroxystyrene, and vinylbenzoic acid.
[0077] Examples of monomers other than the styrene-based monomers include aliphatic monomers and aromatic monomers. The aliphatic monomer includes an aliphatic hydrocarbon. The aromatic monomer may be any aromatic hydrocarbon other than those exemplified as the styrene-based monomer.
[0078] Commercially available copolymers of the above-mentioned styrene-based monomers and aliphatic monomers include, for example, "FTR6100", "FTR6110", and "FTR6125" manufactured by Mitsui Chemicals.
[0079] Commercially available copolymers of the above styrene-based monomers include, for example, "FTR2120", "FTR2140", "FTR8100", and "FTR8120" manufactured by Mitsui Chemicals.
[0080] The softening point of the petroleum resin-based tackifier (B) (measured, for example, by the ring and ball method) is preferably 30 to 200° C., particularly preferably 60 to 180° C., more preferably 70 to 160° C., further preferably 80 to 140° C., and particularly preferably 90 to 130° C. When the softening point is within the above range, the adhesive strength, holding power, and tackiness tend to be excellent.
[0081] The petroleum resin-based tackifier (B) preferably has an acid value of 5 mgKOH / g or less, particularly preferably 3 mgKOH / g or less, further preferably 2 mgKOH / g or less, and particularly preferably 1 mgKOH / g or less. When multiple types of tackifier resins are used in combination, the average thereof is preferably within the above range.
[0082] The petroleum resin-based tackifier (B) preferably has a hydroxyl value of 5 mgKOH / g or less, particularly preferably 3 mgKOH / g or less, further preferably 2 mgKOH / g or less, and particularly preferably 1 mgKOH / g or less. When multiple types of tackifier resins are used in combination, the average of the values is preferably within the above range.
[0083] The acid value and hydroxyl value of the petroleum resin-based tackifier (B) are determined by neutralization titration in accordance with JIS K0070.
[0084] The content of the petroleum resin-based tackifier (B) is 0.01 to 50 parts by weight, more preferably 1 to 40 parts by weight, even more preferably 2 to 30 parts by weight, particularly preferably 3 to 25 parts by weight, especially preferably 4 to 20 parts by weight, and most preferably 5 to 15 parts by weight, relative to 100 parts by weight of the polyester resin (A). When the content is within the above range, the adhesive strength, holding strength, and tackiness are excellent.
[0085] The polyester-based pressure-sensitive adhesive composition of the present invention may contain, in addition to the polyester resin (A) and petroleum resin-based tackifier (B), preferably a hydrolysis inhibitor (C), a crosslinking agent (D), a urethanization catalyst (E), and, if necessary, an antioxidant, etc.
[0086] <Hydrolysis inhibitor (C)> The hydrolysis inhibitor (C) is contained in order to ensure the long-term durability of the polyester-based pressure-sensitive adhesive composition. As the hydrolysis inhibitor (C), a conventionally known one can be used, for example, a compound that reacts with the carboxyl terminal of the polyester resin (A) and bonds thereto, specifically, for example, a compound containing a functional group such as a carbodiimide group, an epoxy group, an oxazoline group, etc. Among these, a carbodiimide group-containing compound is preferred because it has a high effect of eliminating the catalytic activity of the proton derived from the carboxyl terminal.
[0087] As the carbodiimide group-containing compound, a known carbodiimide having one or more carbodiimide groups (-N=C=N-) in the molecule may be used, but in order to improve durability under high temperature and high humidity, a compound having two or more carbodiimide groups in the molecule, i.e., a polyvalent carbodiimide compound, is preferred, and in particular, a compound having three or more, further five or more, and especially seven or more carbodiimide groups in the molecule is preferred. The number of carbodiimide groups in the molecule is usually 50 or less, and if there are too many carbodiimide groups, the molecular structure becomes too large, so compatibility tends to decrease. It is also preferred to use a high molecular weight polycarbodiimide produced by decarboxylation condensation reaction of diisocyanate in the presence of a carbodiimide catalyst.
[0088] Furthermore, in terms of storage stability, it is preferable that the terminal isocyanate group of the high molecular weight polycarbodiimide is blocked with a blocking agent. Examples of the blocking agent include compounds having active hydrogen that reacts with the isocyanate group, or compounds having an isocyanate group. For example, monoalcohols, monocarboxylic acids, monoamines, and monoisocyanates each having one substituent selected from a carboxy group, an amino group, and an isocyanate group are included.
[0089] Examples of such high molecular weight polycarbodiimides include those obtained by subjecting the following diisocyanates to a decarboxylation condensation reaction.
[0090] Examples of such diisocyanates include 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 3,3'-dimethyl-4,4'-diphenylether diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and tetramethylxylylene diisocyanate, which may be used alone or in combination of two or more. Such high molecular weight polycarbodiimides may be synthesized or commercially available products may be used.
[0091] Commercially available examples of the carbodiimide group-containing compound include the Carbodilite (registered trademark) series manufactured by Nisshinbo Chemical Inc. Among these, Carbodilite (registered trademark) V-01, V-02B, V-03, V-04K, V-04PF, V-05, V-07, V-09, and V-09GB are preferred because of their excellent compatibility with the polyester resin (A).
[0092] As the epoxy group-containing compound, for example, a glycidyl ester compound or a glycidyl ether compound is preferable.
[0093] Specific examples of the glycidyl ester compound include benzoic acid glycidyl ester, t-Bu-benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexane carboxylic acid glycidyl ester, pelargonic acid glycidyl ester, stearic acid glycidyl ester, lauric acid glycidyl ester, palmitic acid glycidyl ester, behenic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester, linoleic acid glycidyl ester, linolenic acid glycidyl ester, behenolic acid glycidyl ester, stearolic acid glycidyl ester, terephthalic acid diglycidyl ester, isophthalic acid Examples of the diglycidyl ester include diglycidyl ester of phthalic acid, diglycidyl ester of naphthalenedicarboxylic acid, diglycidyl ester of methyl terephthalic acid, diglycidyl ester of hexahydrophthalic acid, diglycidyl ester of tetrahydrophthalic acid, diglycidyl ester of cyclohexanedicarboxylic acid, diglycidyl ester of adipic acid, diglycidyl ester of succinic acid, diglycidyl ester of sebacic acid, diglycidyl ester of dodecanedioic acid, diglycidyl ester of octadecanedicarboxylic acid, triglycidyl ester of trimellitic acid, and tetraglycidyl ester of pyromellitic acid. These may be used alone or in combination of two or more.
[0094] Specific examples of the glycidyl ether compound include phenyl glycidyl ether, o-phenyl glycidyl ether, 1,4-bis(β,γ-epoxypropoxy)butane, 1,6-bis(β,γ-epoxypropoxy)hexane, 1,4-bis(β,γ-epoxypropoxy)benzene, 1-(β,γ-epoxypropoxy)-2-ethoxyethane, 1-(β,γ-epoxypropoxy)-2-benzyloxyethane, 2,2-bis-[р-(β,γ-epoxypropoxy)phenyl]propane, and bisphenols such as 2,2-bis-(4-hydroxyphenyl)propane and 2,2-bis-(4-hydroxyphenyl)methane, and bisglycidyl polyethers obtained by reacting epichlorohydrin, and these can be used alone or in combination of two or more kinds.
[0095] The oxazoline group-containing compound is preferably a bisoxazoline compound, etc. Specifically, for example, 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline), 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2-oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(4,4-dimethyl-2-oxazoline) 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2'-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline), 2,2'-ethylenebis(2-oxazoline), Examples of suitable tert-butylene bis(4-methyl-2-oxazoline), 2,2'-tetramethylene bis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethane bis(2-oxazoline), 2,2'-cyclohexylene bis(2-oxazoline), 2,2'-diphenylene bis(2-oxazoline), etc., among which 2,2'-bis(2-oxazoline) is most preferred from the viewpoint of reactivity with polyester resin (A). These may be used alone or in combination of two or more.
[0096] It is preferable that the hydrolysis inhibitor (C) has low volatility, and therefore it is preferable to use one having a high number average molecular weight, which is usually 300 to 10,000, and preferably 1,000 to 5,000. In addition, from the viewpoint of hydrolysis resistance, it is preferable to use a hydrolysis inhibitor (C) having a high weight average molecular weight. The weight average molecular weight of the hydrolysis inhibitor (C) is preferably 500 or more, more preferably 1000 or more, even more preferably 2000 or more, and particularly preferably 3000 or more. The upper limit of the weight average molecular weight is usually 50,000. If the molecular weight of the hydrolysis inhibitor (C) is too small, the hydrolysis resistance tends to decrease, whereas if the molecular weight is too large, the compatibility with the polyester resin (A) tends to decrease.
[0097] Among the hydrolysis inhibitors (C), it is preferable to use a carbodiimide group-containing compound, and in this case, the carbodiimide equivalent is preferably 50 to 10,000, particularly 100 to 1,000, and further preferably 150 to 500. The carbodiimide equivalent indicates the chemical formula weight per one carbodiimide group.
[0098] The content of the hydrolysis inhibitor (C) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 5 parts by weight, and further preferably 0.2 to 3 parts by weight, based on 100 parts by weight of the polyester resin (A). If the content is too high, turbidity tends to occur due to poor compatibility with the polyester resin (A), and if the content is too low, sufficient durability tends to be difficult to obtain.
[0099] The content of the hydrolysis inhibitor (C) is preferably optimized depending on the acid value of the polyester resin (A), and the molar ratio [(y) / (x)] of the total number of moles (y) of functional groups of the hydrolysis inhibitor (C) in the polyester pressure-sensitive adhesive composition to the total number of moles (x) of acidic functional groups of the polyester resin (A) in the polyester pressure-sensitive adhesive composition is preferably 0.5≦(y) / (x), particularly preferably 1≦(y) / (x)≦1000, and even more preferably 1.5≦(y) / (x)≦100. If the molar ratio of (y) to (x) is too low, the moisture and heat resistance tends to decrease, whereas if the molar ratio of (y) to (x) is too high, the compatibility with the polyester resin (A) tends to decrease, and the adhesive strength, cohesive strength, and durability tend to decrease.
[0100] <Crosslinking agent (D)> It is preferable that the polyester-based pressure-sensitive adhesive composition of the present invention further contains a crosslinking agent (D). By containing the crosslinking agent (D), the polyester-based resin (A) is crosslinked with the crosslinking agent (D) to provide excellent cohesive strength, thereby improving the performance as a pressure-sensitive adhesive.
[0101] Examples of such crosslinking agents (D) include compounds having a functional group that reacts with at least one of the hydroxyl group and the carboxyl group contained in the polyester resin (A), such as polyisocyanate-based compounds and polyepoxy-based compounds. Among these, it is particularly preferable to use polyisocyanate-based compounds, since they can achieve a good balance between initial adhesion, mechanical strength, and heat resistance.
[0102] Examples of such polyisocyanate compounds include aromatic isocyanate compounds such as tolylene diisocyanate compounds such as 2,4-tolylene diisocyanate and 2,6-tolylene diisocyanate, xylylene diisocyanate compounds such as 1,3-xylylene diisocyanate, diphenylmethane compounds such as diphenylmethane-4,4-diisocyanate, and naphthalene diisocyanate compounds such as 1,5-naphthalene diisocyanate; isophorone diisocyanate, 1,4-cyclohexane diisocyanate, and the like. Alicyclic isocyanate compounds such as 4,4'-dicyclohexylmethane diisocyanate, methylcyclohexane diisocyanate, isopropylidenedicyclohexyl-4,4'-diisocyanate, 1,3-diisocyanatomethylcyclohexane, and norbornane diisocyanate; aliphatic isocyanate compounds such as hexamethylene diisocyanate and trimethylhexamethylene diisocyanate; and adducts, biuret compounds, and isocyanurates of the above-mentioned isocyanate compounds. The above-mentioned polyisocyanate compounds may also be used in which the isocyanate portion is blocked with phenol, lactam, or the like. These polyisocyanate compounds may be used alone or in combination of two or more.
[0103] The content of the crosslinking agent (D) can be appropriately selected depending on the molecular weight of the polyester resin (A) and the intended use. In general, the crosslinking agent (D) is preferably contained in a ratio such that the reactive group contained in the crosslinking agent (D) is 0.2 to 10 equivalents per equivalent of at least one of the hydroxyl group and the carboxy group contained in the polyester resin (A), particularly preferably 0.5 to 5 equivalents, further preferably 0.5 to 3 equivalents, and further preferably 0.5 to 1.5 equivalents. If the equivalent number of the reactive groups contained in the crosslinking agent (D) is too small, the cohesive strength tends to decrease, whereas if it is too large, the flexibility tends to decrease.
[0104] The content of the crosslinking agent (D) is preferably 0.1 to 20 parts by weight, particularly preferably 0.2 to 15 parts by weight, even more preferably 0.3 to 10 parts by weight, even more preferably 0.5 to 5 parts by weight, and especially preferably 1 to 3 parts by weight, per 100 parts by weight of the polyester resin (A). If the content of the crosslinking agent (D) is too low, the cohesive strength tends to decrease, whereas if the content is too high, the flexibility tends to decrease.
[0105] In the reaction between the polyester resin (A) and the crosslinking agent (D), organic solvents that do not have functional groups that react with the components (A) and (D), such as esters such as ethyl acetate and butyl acetate, ketones such as methyl ethyl ketone and methyl isobutyl ketone, aromatics such as toluene and xylene, etc., can be used alone or in combination of two or more kinds.
[0106] <Urethanization catalyst (E)> From the viewpoint of reaction rate, the polyester-based pressure-sensitive adhesive composition of the present invention more preferably contains a urethanization catalyst (E).
[0107] Examples of the urethanization catalyst (E) include organometallic compounds, tertiary amine compounds, etc. These can be used alone or in combination of two or more kinds.
[0108] Examples of the organometallic compound include zirconium-based compounds, iron-based compounds, tin-based compounds, titanium-based compounds, lead-based compounds, cobalt-based compounds, and zinc-based compounds. Examples of the zirconium compound include zirconium naphthenate and zirconium acetylacetonate. Examples of iron-based compounds include iron acetylacetonate and iron 2-ethylhexanoate. Examples of the tin compounds include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate. Examples of titanium compounds include dibutyltitanium dichloride, tetrabutyltitanium, and butoxytitanium trichloride. Examples of lead-based compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate. Examples of the cobalt-based compounds include cobalt 2-ethylhexanoate and cobalt benzoate. Examples of zinc-based compounds include zinc naphthenate and zinc 2-ethylhexanoate.
[0109] Examples of the tertiary amine compound include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undecene-7.
[0110] Among these urethane catalysts (E), in terms of reaction speed and pot life of the adhesive layer, organometallic compounds are preferred, and zirconium compounds are particularly preferred. Furthermore, the urethane catalyst (E) is preferably used in combination with acetylacetone as a catalytic action inhibitor. The inclusion of acetylacetone is preferred in that the catalytic action at low temperatures is inhibited, and the pot life is extended.
[0111] In the polyester-based adhesive composition of the present invention, in addition to the above-mentioned polyester-based resin (A), petroleum resin-based tackifier (B), hydrolysis inhibitor (C), crosslinking agent (D), and urethanization catalyst (E), additives such as antioxidants such as hindered phenols, softeners, ultraviolet absorbers, stabilizers, antistatic agents, tackifiers other than the petroleum resin-based tackifier (B), and other powdery or particulate additives such as inorganic or organic fillers, metal powders, and pigments can be blended within the range that does not impair the effects of the present invention. These can be used alone or in combination of two or more kinds.
[0112] The polyester-based pressure-sensitive adhesive of the present invention is obtained by crosslinking the above-mentioned polyester-based pressure-sensitive adhesive composition.
[0113] The pressure-sensitive adhesive sheet of the present invention has a pressure-sensitive adhesive layer containing the above-mentioned polyester-based pressure-sensitive adhesive, and such a pressure-sensitive adhesive layer is preferably formed on one or both sides of a supporting substrate. In the present invention, the term "sheet" is used to include the meanings of "film" and "tape."
[0114] <Adhesive sheet> The pressure-sensitive adhesive sheet can be produced, for example, as follows. Such a pressure-sensitive adhesive sheet can be produced according to a publicly known general pressure-sensitive adhesive sheet production method. For example, the polyester-based pressure-sensitive adhesive composition is applied onto a substrate, dried, and a release sheet is attached to the opposite surface of the pressure-sensitive adhesive layer, followed by curing as necessary to obtain the pressure-sensitive adhesive sheet of the present invention, which has a substrate and a pressure-sensitive adhesive layer containing a polyester-based pressure-sensitive adhesive, with the pressure-sensitive adhesive layer being provided on at least one surface of the substrate.
[0115] Alternatively, the pressure-sensitive adhesive sheet of the present invention can be obtained by coating the polyester-based pressure-sensitive adhesive composition on a release sheet, drying the composition, laminating a substrate to the opposite surface of the pressure-sensitive adhesive layer, and curing the composition if necessary.
[0116] Furthermore, by forming a pressure-sensitive adhesive layer on a release sheet and laminating a release sheet to the opposite side of the pressure-sensitive adhesive layer, a substrateless type pressure-sensitive adhesive sheet can be produced that has a pressure-sensitive adhesive layer containing a polyester-based pressure-sensitive adhesive and does not have a substrate.
[0117] When using the obtained pressure-sensitive adhesive sheet or substrate-less type pressure-sensitive adhesive sheet, the release sheet is peeled off from the pressure-sensitive adhesive layer, and the pressure-sensitive adhesive layer is attached to an adherend.
[0118] Examples of the substrate include polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyethylene fluoride resins such as polyvinyl fluoride, polyvinylidene fluoride, and polyethylene fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; polystyrene; polycarbonate; polyarylate; polyimide; and sheets made of at least one synthetic resin selected from the group consisting of cycloolefin polymers; metal foils of aluminum, copper, and iron; paper such as fine paper and glassine paper; and woven and nonwoven fabrics made of glass fiber, natural fibers, synthetic fibers, and the like. These substrates can be used as a single layer or as a multi-layer structure in which two or more types are laminated.
[0119] Among these, substrates made of polyethylene terephthalate and polyimide are particularly preferred, with polyethylene terephthalate being particularly preferred in terms of excellent adhesion to pressure-sensitive adhesives.
[0120] The substrate may be a foam substrate, for example, a foam sheet made of a synthetic resin foam such as polyurethane foam, polyethylene foam, polyacrylate foam, etc. Among these, polyethylene foam and polyacrylate foam are preferred because of their excellent balance between conformability to the adherend and adhesive strength.
[0121] The thickness of the substrate is, for example, preferably from 1 to 1000 μm, particularly preferably from 2 to 500 μm, and further preferably from 3 to 300 μm.
[0122] As the release sheet, for example, a sheet made of various synthetic resins exemplified above as the base material, paper, cloth, nonwoven fabric, etc., which has been subjected to a release treatment can be used. As the release sheet, it is preferable to use a silicone-based release sheet.
[0123] The polyester-based pressure-sensitive adhesive composition may be applied using, for example, a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, a comma coater or the like.
[0124] The conditions for the above-mentioned aging treatment are generally room temperature (23°C) to 70°C, and the time is generally 1 to 30 days. Specifically, the treatment may be performed under conditions such as 23°C for 1 to 20 days, preferably 23°C for 3 to 14 days, or 40°C for 1 to 10 days.
[0125] As for drying conditions, the drying temperature is preferably 60 to 140° C., particularly preferably 80 to 120° C., and the drying time is preferably 0.5 to 30 minutes, particularly preferably 1 to 5 minutes.
[0126] The thickness of the adhesive layer of the above-mentioned adhesive sheet and substrate-less double-sided adhesive sheet is preferably 2 to 500 μm, particularly preferably 5 to 200 μm, and further preferably 10 to 100 μm. If the thickness of the adhesive layer is too thin, the adhesive strength tends to decrease, while if it is too thick, it becomes difficult to apply uniformly and problems such as air bubbles in the coating film tend to occur. When considering impact absorption, it is preferable to make the thickness 50 μm or more.
[0127] The thickness of the adhesive layer is determined by subtracting the measured thickness of the components other than the adhesive layer from the measured thickness of the entire adhesive sheet using a Mitutoyo ID-C112B.
[0128] The gel fraction of the adhesive layer of the adhesive sheet is preferably 5% by weight or more from the viewpoint of durability and adhesive strength, particularly preferably 6 to 80% by weight, further preferably 7 to 60% by weight, more preferably 10 to 40% by weight, particularly preferably 15 to 35% by weight, and most preferably 20 to 30% by weight. If the gel fraction is too low, the cohesive strength tends to decrease, resulting in a decrease in holding power. However, if the gel fraction is too high, the cohesive strength tends to increase, resulting in a decrease in adhesive strength.
[0129] The gel fraction is an indication of the degree of crosslinking, and is calculated, for example, by the following method. That is, an adhesive sheet (without a release sheet) in which an adhesive layer is formed on a polymer sheet (e.g., a PET film, etc.) serving as a substrate is wrapped in a 200-mesh SUS wire netting, and immersed in toluene at 23°C for 24 hours, and the weight percentage of the insoluble adhesive component remaining in the wire netting after immersion relative to the weight of the adhesive component before immersion is taken as the gel fraction. However, the weight of the substrate is subtracted.
[0130] Furthermore, such a pressure-sensitive adhesive sheet may be protected by providing a release sheet on the outer side of the pressure-sensitive adhesive layer, if necessary. In a pressure-sensitive adhesive sheet in which the pressure-sensitive adhesive layer is formed on one side of a substrate, the substrate may be subjected to a release treatment on the side opposite to the pressure-sensitive adhesive layer, and the release-treated surface may be used to protect the pressure-sensitive adhesive layer.
[0131] The polyester-based pressure-sensitive adhesive of the present invention can be used for bonding various components, and is particularly used as a single-sided or double-sided pressure-sensitive adhesive sheet used for bonding optical components, for fixing components of portable electronic devices, and for fixing electronic components. EXAMPLES
[0132] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by weight unless otherwise specified. In the following examples, the glass transition temperature, number average molecular weight, weight average molecular weight, acid value, hydroxyl value, ester bond concentration and heat of fusion of crystals of the polyester resin (A) were determined according to the methods described above.
[0133] Prior to the examples, the following components were prepared.
[0134] [Production of polyester resin] The molar percentages of structural units derived from the final components of polycarboxylic acids (hereinafter sometimes abbreviated as "final component percentages") described in the following manufacturing examples indicate the molar percentages when the total amount of polycarboxylic acids is taken as 100 mol %. Furthermore, the mole percentages of the final polyol components described in the following Production Examples indicate the mole percentages when the total amount of polyols is taken as 100 mole percent.
[0135] [Polyester resin (A-1)] In a reaction vessel equipped with a heater, a thermometer, a stirrer, a rectification column, a nitrogen inlet tube and a vacuum device, 94.6 parts (20 mol%) of isophthalic acid (IPA) (a1-1-1) and 460.8 parts (80 mol%) of sebacic acid (SebA) as polyvalent carboxylic acids (a1), 128.3 parts (50 mol%) of 1,4-butanediol (1.4BG) (a2-3) as polyols (a2), 296.6 parts (100 mol%) of neopentyl glycol (NPG) (a2-2), 5.7 parts (1.5 mol%) of trimethylolpropane (TMP), and 14 parts (0.3 mol%) of hydrogenated polybutadiene polyol (a2-1) (manufactured by Nippon Soda Co., Ltd., "GI-1000"), and 0.05 parts of zinc acetate as a catalyst were charged, and the internal temperature was gradually raised to 250°C, and an esterification reaction was carried out over 4 hours. Thereafter, the internal temperature was raised to 260° C., 0.05 parts of tetrabutyl titanate was charged as a catalyst, the pressure was reduced to 1.33 hPa, and a polymerization reaction was carried out over 3 hours to produce a polyester resin (A-1). The final component ratio of the obtained polyester resin (A-1) was isophthalic acid / sebacic acid=20 mol% / 80 mol% as polyvalent carboxylic acids (a1), and 1,4-butanediol / neopentyl glycol / trimethylolpropane / hydrogenated polybutadiene polyol=33.7 mol% / 64.5 mol% / 1.5 mol% / 0.3 mol% as polyols (a2), and various physical properties were as shown in Table 1. The content of structural units derived from the hydrogenated polybutadiene structure-containing compound in the polyester resin (A-1) was 1.7% by weight, and the heat of crystalline fusion was 0 J / g.
[0136] [Tackifiers (B), (B')] (B-1): Copolymer of styrene monomer and aliphatic monomer (number average molecular weight (Mn) 860, weight average molecular weight (Mw) 1210, glass transition temperature (Tg) 30°C, softening point 95°C, acid value less than 1 mgKOH / g, hydroxyl value less than 1 mgKOH / g (Mitsui Chemicals, Inc., "FTR-6100") (B-2): Copolymer of styrene monomer and aliphatic monomer (number average molecular weight (Mn) 1150, weight average molecular weight (Mw) 1950, glass transition temperature (Tg) 65°C, softening point 125°C, acid value less than 1 mgKOH / g, hydroxyl value less than 1 mgKOH / g (Mitsui Chemicals, Inc., "FTR-6125") (B-3): Copolymer of styrene monomer (number average molecular weight (Mn) 820, weight average molecular weight (Mw) 1240, glass transition temperature (Tg) 35°C, softening point 100°C, acid value less than 1 mgKOH / g, hydroxyl value less than 1 mgKOH / g (Mitsui Chemicals, Inc., "FTR-8100") (B'-1): Terpene phenol-based tackifier (number average molecular weight (Mn) 500, softening point 80°C, acid value less than 1 mgKOH / g, hydroxyl value 70 mgKOH / g (manufactured by Yasuhara Chemical Co., Ltd., "T80") (B'-2): Aliphatic monomer copolymer (number average molecular weight (Mn) 370, weight average molecular weight (Mw) 500, glass transition temperature (Tg) -31°C, softening point 10°C, acid value less than 1 mgKOH / g, hydroxyl value less than 1 mgKOH / g (manufactured by Cray Valley, "Wingtack10")
[0137] [Hydrolysis inhibitor (C)] (C-1): Polyvalent carbodiimide compound (Nisshinbo Chemical Co., Ltd., "Carbodilite V-09GB, solid content 70%")
[0138] [Crosslinking agent (D)] (D-1): Trimethylolpropane / tolylene diisocyanate adduct (manufactured by Tosoh Corporation, "Coronate L55E, solids concentration 55%")
[0139] [Urethanization catalyst (E)] (E-1): Zirconium-based compound diluted with acetylacetone to a solids concentration of 1% (Matsumoto Fine Chemical Co., Ltd., "Orgatics ZC-150")
[0140] (Examples 1 to 4, Comparative Examples 1 to 6) The polyester resin (A) obtained above was diluted with ethyl acetate to a solid content concentration of 50%, and the tackifier (B) or (B'), hydrolysis inhibitor (C), crosslinking agent (D), and urethanization catalyst (E) were added to this polyester resin (A) (100 parts as solid content) in the composition shown in Table 2 (solid content ratio), and the mixture was stirred and mixed to obtain a polyester adhesive composition. Using the polyester-based pressure-sensitive adhesive compositions obtained in the above Examples and Comparative Examples, pressure-sensitive adhesive sheets were produced as described below and evaluated as described below. The gel fraction of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet was also determined according to the method described above.
[0141] <Preparation of adhesive sheet with one-sided release film> The polyester-based adhesive compositions obtained in the Examples and Comparative Examples were applied onto a 38 μm-thick PET film ("Lumirror T60" manufactured by Toray Industries, Inc.) using an applicator and dried at 100° C. for 3 minutes to obtain adhesive sheets with a PET film having an adhesive layer thickness of 25 μm. Next, the surface of the adhesive layer of the obtained adhesive sheet with PET film was covered with a 38 μm thick PET release film (Mitsui Chemicals Tocello, SP-PET-01-BU) and subjected to aging treatment at 40°C for 4 days to obtain an adhesive sheet with a one-sided release film.
[0142] (Adhesive sheet evaluation) [Adhesive strength] The pressure-sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 25 mm x 200 mm under an environment of 23 ° C and 50% RH, the release film was peeled off, and the pressure-sensitive adhesive layer side was pressed and attached to (1) a mirror-finished stainless steel plate (SUS-BA plate), (2) a PET film backed by the SUS-BA plate, and (3) a polyethylene plate (PE) by rolling a 2 kg roller twice back and forth, and then left to stand for 30 minutes under the same atmosphere, and then the 180 degree peel strength (N / 25 mm) was measured at a peel speed of 300 mm / min using an autograph (Shimadzu Corporation, "Autograph AG-X 50N"). The evaluation criteria are as follows. (Evaluation Criteria) ○ Greater than 10N / 25mm △: More than 5N / 25mm and 10N / 25mm or less ×...5N / 25mm or less
[0143] [Holding force] The pressure sensitive adhesive sheet with one-sided release film obtained above was cut to a size of 25mm x 50mm in an environment of 23°C and 50% RH, the release film was then peeled off, and the sheet was pressed and attached to a stainless steel plate (SUS304) by rolling a 2kg roller back and forth twice (attached area 25mm x 25mm), and the holding power was measured for 24 hours at 40°C under a load of 1kg using a creep tester (Tester Sangyo Co., Ltd., holding power tester BE-501 with high temperature and humidity chamber). The evaluation criteria are as follows. (Evaluation Criteria) 〇 No misalignment △ Misalignment is 1.0 mm or less × Misalignment is greater than 1.0 mm or the item has fallen
[0144] [Tackiness] The pressure sensitive adhesive sheet with one-sided release film obtained above was cut into a size of 25mm x 100mm in an environment of 23℃ and 50% RH, and after setting it at an angle of 30° using an inclined ball tack tester, the release film was peeled off, and 32 types of bearing balls with diameters from 1 / 32 to 1 inch were rolled over a sliding distance of 100mm, and the maximum number of balls that remained on the adhesive surface for 30 seconds or more was taken as the ball tack value. The evaluation criteria are as follows. (Evaluation Criteria) 〇Ball No. 9 or higher △···Ball No.7~8 × Ball No. 6 or smaller
[0145] [Table 1] (last page)
[0146] [Table 2] (last page)
[0147] The results in Table 2 above show that the adhesive sheets obtained from the polyester-based adhesive compositions of Examples 1 to 4, which use a polyester-based resin (A) and a petroleum resin-based tackifying resin (B) having a specific number average molecular weight in a specific content ratio, are excellent in adhesive strength, holding power, and tackiness. In contrast, the adhesive sheet obtained from the polyester adhesive composition of Comparative Example 1, which does not use a petroleum resin-based tackifier resin (B) having a specific number average molecular weight, had a holding power, but was poor in adhesion and tackiness. The adhesive sheet obtained from the polyester adhesive composition of Comparative Example 2, which used a large amount of petroleum resin-based tackifier resin (B) having a specific number average molecular weight, was poor in all of adhesion, holding power, and ball tackiness. The adhesive sheets obtained from the polyester adhesive compositions of Comparative Examples 3 and 4, which used a terpene tackifier resin, had a holding power, but were poor in adhesion and tackiness. Furthermore, the adhesive sheets obtained from the polyester adhesive compositions of Comparative Examples 5 and 6, which used a petroleum resin-based tackifier resin with a small number average molecular weight, were excellent in holding power, but were poor in adhesion and tackiness. From this, it can be seen that the polyester adhesive composition containing a polyester resin (A) and a petroleum resin-based tackifier resin (B) having a specific number average molecular weight in a specific ratio have excellent adhesive properties. [Industrial Applicability]
[0148] The polyester-based pressure-sensitive adhesive composition of the present invention is excellent in adhesive strength, holding power and tackiness. Therefore, polyester-based pressure-sensitive adhesives and pressure-sensitive adhesive sheets using the same can be suitably used for bonding electronic components, optical components, building components, and the like.
Claims
1. The composition comprises a polyester resin (A) having a structural unit derived from a polyvalent carboxylic acid (a1) and a structural unit derived from a polyol (a2), and a petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8,000, The polyester resin (A) has a glass transition temperature of −80 to 20° C. and a heat of crystalline fusion of 3 J / g or less; The polyester-based adhesive composition is characterized in that the content of the petroleum resin-based tackifier (B) having a number average molecular weight of 400 to 8000 is 0.01 to 50 parts by weight per 100 parts by weight of the polyester resin (A).
2. 2. The polyester-based pressure-sensitive adhesive composition according to claim 1, wherein the petroleum resin-based tackifier (B) has an aromatic ring structure.
3. 3. The polyester-based pressure-sensitive adhesive composition according to claim 1, wherein the petroleum resin-based tackifier (B) has a softening point of 30 to 200°C.
4. 4. The pressure-sensitive adhesive composition according to claim 1, wherein the petroleum resin-based tackifier (B) has an acid value of 5 mgKOH / g or less.
5. 5. The polyester-based pressure-sensitive adhesive composition according to claim 1, wherein the polyester-based resin (A) has an ester bond concentration of 3 to 9 mmol / g.
6. The polyester-based pressure-sensitive adhesive composition according to any one of claims 1 to 5, further comprising a hydrolysis inhibitor (C).
7. The polyester-based pressure-sensitive adhesive composition according to any one of claims 1 to 6, further comprising a crosslinking agent (D).
8. A polyester-based pressure-sensitive adhesive obtained by crosslinking the polyester-based pressure-sensitive adhesive composition according to any one of claims 1 to 7.
9. A pressure-sensitive adhesive sheet comprising a pressure-sensitive adhesive layer containing the polyester-based pressure-sensitive adhesive according to claim 8.
10. 9. An adhesive sheet comprising a substrate and an adhesive layer containing the polyester-based adhesive according to claim 8, wherein the adhesive layer is provided on at least one surface of the substrate.
11. 9. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer containing the polyester-based pressure-sensitive adhesive according to claim 8, which is a substrate-less type pressure-sensitive adhesive sheet having no substrate.
Citation Information
Patent Citations
Skin friendly adhesive
EP2853573A1
Tackifier resin for polyester-based adhesive and polyester-based adhesive composition
JP1998298528A
Heat and pressure-sensitive adhesive, heat and pressure-sensitive adhesive sheet and application method thereof
JP2007270050A
Pressure-sensitive adhesive sheet for surface protection
JP2011088958A
Adhesive layer, adhesive tape, and double-sided adhesive tape
JP2014169419A